Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.3389/fchem.2019.00431
|View full text |Cite
|
Sign up to set email alerts
|

Design of an Antifungal Surface Embedding Liposomal Amphotericin B Through a Mussel Adhesive-Inspired Coating Strategy

Abstract: Microbial colonization of urinary catheters remains a serious problem for medicine as it often leads to biofilm formation and infection. Among the approaches reported to deal with this problem, surfaces functionalization to render them with antimicrobial characteristics, comprises the most promising one. Most of these strategies, however, are designed to target bacterial biofilms, while fungal biofilms are much less taken into account. In real-life settings, fungi will be inevitably found in consortium with ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 45 publications
0
23
0
Order By: Relevance
“…Antimicrobial properties of prepared surfaces were evaluated as previously reported, with some modifications [27]. Briefly, 20 μL of a bacterial suspension adjusted to approximately 10 6 CFU mL − 1 were added on top of each surface and incubated under static conditions at 37 • C. When the drop was dried, coupons were placed on a TSA plate, with the face exposed to bacterial suspension in contact with the agar, and they were incubated at 37 • C for 24 h. Bacterial growth was then evaluated for the tested surfaces and tabulated as "+" for growth and "-" for no visible growth.…”
Section: Antimicrobial and Leaching Properties Of Modified Surfacesmentioning
confidence: 99%
See 1 more Smart Citation
“…Antimicrobial properties of prepared surfaces were evaluated as previously reported, with some modifications [27]. Briefly, 20 μL of a bacterial suspension adjusted to approximately 10 6 CFU mL − 1 were added on top of each surface and incubated under static conditions at 37 • C. When the drop was dried, coupons were placed on a TSA plate, with the face exposed to bacterial suspension in contact with the agar, and they were incubated at 37 • C for 24 h. Bacterial growth was then evaluated for the tested surfaces and tabulated as "+" for growth and "-" for no visible growth.…”
Section: Antimicrobial and Leaching Properties Of Modified Surfacesmentioning
confidence: 99%
“…This coating strategy, based on a mussel adhesive protein, was first described in 2007 by Messersmith and co-workers and it comprises the immersion of substrates in an alkaline solution of dopamine, which selfpolymerization results in the deposition of an adhesive film with nanometer thickness [26]. It has been successfully applied for the immobilization of antifungals, antimicrobial peptides and enzymes to render the surfaces of biomaterials with anti-infective properties [27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…PDA deposited onto the polydimethylsiloxane (PDMS) surface has been used to tether synthetic antimicrobial cysteinylated tryptophane–arginine-rich peptide (CWFWKWWRRRRR-NH 2 ) (CWR11) that displayed antimicrobial functionality over 21 days on catheter-relevant surfaces to combat catheter-associated urinary tract infections ( Lim et al, 2015 ). Similarly, immobilization of liposomal amphotericin B (LAmB) on a PDA-coated PDMS surface, a material commonly used in the manufacturing of urinary catheters, was shown to impart the ability to resist Candida albicans colonization ( Alves et al, 2019 ).…”
Section: Cationic Charge Enriched Pda-fabricated Surfaces: Effect On mentioning
confidence: 99%
“…AmBisome has a strong affinity for Candida cells, electrostatically interacting with the cell wall before binding to the cell membrane at sites of high ergosterol content ( Soo Hoo, 2017 ), which may promote their activity against biofilm Candida cells, which have been shown to have thicker cell walls ( Nett et al, 2007 ). Liposomal amphotericin B has also been immobilized on biomaterial surfaces for the prevention of biofilm formation ( Alves et al, 2019 ). In our recent work, we have shown that liposomes encapsulating anidulafungin, the latest echinocandin approved by the FDA, are effective against mature C. albicans biofilms, reducing metabolic activity to approximately 46% compared to untreated controls over 24 h. Biofilms treated with an equivalent concentration of free anidulafungin did not reduce metabolic activity, further emphasizing the importance of nanoformulations in the treatment of Candida biofilms ( Vera-González et al, 2020 ).…”
Section: Nanoparticles For the Prevention Of Fungal Cell Attachment Amentioning
confidence: 99%